SLC6A14 Impacts Cystic Fibrosis Lung Disease Severity via mTOR and Epithelial Repair Modulation - Mercier, Julia; Calmel, Claire; Mésinèle, Julie; Sutanto, Erika; Merabtene, Fatiha; Longchampt, Elisabeth; Sage, Edouard; Kicic, Anthony; Boëlle, Pierre-Yves; Corvol, Harriet; Ruffin, Manon; Guillot, Loïc (Frontiers in Molecular Biosciences, 2022)
Cystic fibrosis (CF), due to variants in CFTR gene, is associated with chronic infection/inflammation responsible for airway epithelium alteration and lung function decline. Modifier genes induce phenotype variability between people with CF (pwCF) carrying the same CFTR variants. Among these, the gene encoding for the amino acid transporter SLC6A14 has been associated with lung disease severity and age of primary airway infection by the bacteria Pseudomonas aeruginosa. In this study, we investigated whether the single nucleotide polymorphism (SNP) rs3788766, located within SLC6A14 promoter, is associated with lung disease severity in a large French cohort of pwCF. We also studied the consequences of this SNP on SLC6A14 promoter activity using a luciferase reporter and the role of SLC6A14 in mammalian target of rapamycin (mTOR) signaling pathway and airway epithelial repair. We confirm that SLC6A14 rs3788766 SNP is associated with lung disease severity in pwCF (p=0.020; n=3,257, pancreatic insufficient, aged 6 to 40 years old), with the minor allele G being deleterious. In bronchial epithelial cell lines deficient for CFTR, SLC6A14 promoter activity is reduced in the presence of the rs3788766 G allele. SLC6A14 inhibition with a specific pharmacological blocker reduced 3H-arginine transport, mTOR phosphorylation and bronchial epithelial repair rates in wound healing assays. To conclude, our study highlights that SLC6A14 genotype might affect lung disease severity of people with cystic fibrosis via mTOR and epithelial repair mechanisms modulation in the lung.